Features of vortex trace propagation for aircraft with propellers - A. I. Zhelannikov (Научный вестник МГТУ ГА, 2023)
The article presents the results of a study of the characteristics of the wake vortex of aircraft with turboprop engines. Using the example of the An-12 aircraft, it is shown that rotating propellers make a noticeable contribution to the propagation of the vortex trail behind the aircraft. This is proved by some studies, as well as numerous observations. It also describes a technique for studying the wake vortex of aircraft with propellers. The method is based on the method of discrete vortices. The relevance of such studies is due to the growing interest of carrier companies in aircraft with turboprop engines. It has been proven that when transporting passengers and cargo on such vessels over distances of 700–800 km, maintenance and fuel costs are reduced by about 30–40%. Therefore, the fleet of turboprop aircraft, such as An-22, An-70, An-12, as well as Tu-95, Il-38, C-130, etc., has been preserved so far. New turboprop aircraft are being developed and put into operation: A-400M, Il-114, Il-112M. The vortex trail behind such aircraft also poses a danger to other aircraft flying behind. A feature of the propagation of the wake vortex behind aircraft with propellers is the interaction of vortices coming off the airframe and vortices from the propellers. As a result, due to the rotation of all the screws in one direction, symmetry is broken in the propagation of vortices descending from the right and left halves of the wing. Therefore, it is important to understand how differently the vortices that descend from the airframe of an aircraft with turboprop engines behave. For the convenience of the study, the method of accounting for the effect of vortices from screws is integrated into a special calculation and software package, also based on the method of discrete vortices. In it, when calculating the characteristics of the wake vortex, the flight weight, speed and altitude of the aircraft, its flight configuration, atmospheric conditions, proximity of the earth, axial velocity in the core of the vortex and some other factors are taken into account. This complex has passed the necessary testing and state registration. A number of measures were carried out to validate and verify the developed complex, confirming the operability of the programs included in it and the reliability of the results obtained from it. The results of the study of the characteristics of the wake vortex behind the Antonov-12 aircraft in the form of vertical velocity spectra and fields of perturbed velocities at various distances from it are presented. It is shown that propellers noticeably affect the propagation of the wake vortex behind turboprop aircraft. This circumstance must be taken into account by the crews of aircraft flying behind such aircraft.